Estimation of magma overpressure from partially exposed dykes - A new approach. (March 2023) - Biswas, Sirshendu Kumar; Saha, Kuntal; Das, Gourav; Mondal, Tridib Kumar
Abstract: We present a new method to estimate full length and maximum thickness of dykes from their partial exposures having at least one tip. The method is particularly applicable to dykes which originate as dominantly opening mode fractures. The idealized canonical model for Mode I fracture shows it to open up in the shape of an ellipse. We solve the equation of this ellipse using every possible combination of two points lying on the dyke margin measured from the observed tip to acquire the results. The method has been validated with observations made on felsic dykes found within intrusive porphyritic granitoids of Chotanagpur Granite Gneiss Complex (CGGC), Purulia, India which are completely exposed (showing tips at both ends) or have an exposed centre with at least one tip. The method has also been tested against published data collected from incomplete dyke outcrops found in the caldera walls of Miyake-jima volcano, Japan. Acquired results are found to be in good agreement with the ones estimated through a previously published method. The present method has been successfully employed to calculate the aspect ratios (maximum thickness/total length) of partially exposed mafic dykes emplaced within younger granite of Chitradurga Schist Belt, Western Dharwar Craton, India. We comment on the magma overpressure ranges and depth of origin of these dykes and on the fracture toughness of the host granite. Highlights: We propose a new method to calculate aspect ratio of dykes (Mode-I cracks) from their incomplete outcrops. The results are acquired by solving the equation of an ellipse with the origin at its vertex. The method has been validated with ground as well as published data and produce reasonable results on application.